A Case of Chromosome 22q11.2 Deletion Syndrome with White Matter Abnormalities and Hypernasal Speech: Importance of Extracardiac Symptoms for Earlier Diagnosis - Fujioka, Kaoru; Kanemura, Hideaki; Tando, Tomoko; Aihara, Masao (Journal of Pediatric Neurology, 2019)
Chromosome 22q11.2 deletion syndrome (22q11.2DS) is one of the most common genetic syndromes. The varying presentation and severity of this syndrome result in diagnostic delays, especially in patients without cardiac malformation or characteristic features. We report a noncardiac case of 22q11.2DS with white matter abnormalities and velopharyngeal insufficiency. The recognition of white matter abnormalities as a feature of 22q11.2DS contributed to early diagnosis. Diagnostic delay could lead to inappropriate management and unfavorable outcomes. Increased awareness of the various minor features of 22q11.2DS may enable clinicians to diagnose this syndrome earlier and provide appropriate medical management.
Keywords: 22q11.2 deletion syndrome; white matter abnormality; earlier diagnosis